Hyzine Website-Based E-Books to Improve Learning Outcomes of Social Studies Elementary School - Rizqi, Iffana Fatikha; Sari, Elok Fariha (Universitas Pendidikan Ganesha, 2024)
The use of digital teaching materials is still rare for elementary school education in Indonesia. Currently, learning is still dominated by conventional learning. The purpose of this research is to develop e-books on elementary social studies content that are effective and of high quality, and support the improvement of student learning outcomes. This research is categorized as research and development (R&D) by applying the Borg and Gall model. In the process of collecting data through interviews, expert validation, response questionnaires, and pretest and post-test sheets. This research resulted in, among others: (1) the e-book is very feasible to use, (2) from the results of the response questionnaire the e-book is declared very practical (90.5%), (3) the e-book is proven to be effective based on the results of the N-gain test (58.9%), where there is an increase in the average post-test score than the average pretest score. These results indicate that the e-book is adequately and effectively used. The implication of the development of e-books in this study is that this Hyzine website-based e-book can support the improvement of learning outcomes of social studies content in grade IV students of elementary school.